2019
DOI: 10.4250/jcvi.2019.27.e8
|View full text |Cite
|
Sign up to set email alerts
|

Modified Tricuspid Annular Plane Systolic Excursion for Assessment of Right Ventricular Systolic Function

Abstract: BACKGROUNDTricuspid annular plane systolic excursion (TAPSE) has become a popular tool for assessing right ventricular (RV) systolic function because of its ease of application. TAPSE using transesophageal echocardiography (TEE) is limited by alignment with the lateral wall of the RV. Modified TAPSE (m-TAPSE) is a novel method for measuring TAPSE. m-TAPSE is the difference in the ‘apical to lateral tricuspid annulus distance’ during diastole and systole. The aim of the present study was to compare prospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
0
11
0
2
Order By: Relevance
“…Based on intraobserver analysis, the authors' data showed that all parameters were reproducible for the validated data. In conclusion, Dhawan et al13) showed that m-TAPSE was correlated with both conventional TAPSE and RV-FAC. RV-FAC was validated to be a strong estimate parameter of RV function 8)…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…Based on intraobserver analysis, the authors' data showed that all parameters were reproducible for the validated data. In conclusion, Dhawan et al13) showed that m-TAPSE was correlated with both conventional TAPSE and RV-FAC. RV-FAC was validated to be a strong estimate parameter of RV function 8)…”
mentioning
confidence: 73%
“…To the best of my knowledge, Morita et al9) previously reported that m-TAPSE was validated as having a good correlation to RV-FAC and could be considered an eligible parameter to evaluate RV systolic function. Beyond the previous study, Dhawan et al13) suggested that m-TAPSE for evaluating RV function is possibly useful in a busy intraoperative setting and is not dependent on image quality by “prospectively” comparing m-TAPSE with three parameters: m-TAPSE on TEE, TAPSE measured by TTE, and RV-FAC on TEE. One of the strengths of this study is presentation of the data from TTE and TEE simultaneously measured and recorded post-induction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tricuspid annular plane systolic excursion (TAPSE) is one of the verified methods for assessing RV systolic function. In TEE, the modified TAPSE can be considered an alternative method for evaluating the RV systolic function, especially at the busy operating room 14 …”
Section: Discussionmentioning
confidence: 99%
“…In TEE, the modified TAPSE can be considered an alternative method for evaluating the RV systolic function, especially at the busy operating room. 14 If an accurate diagnosis has been made, veno-arterial ECMO may be helpful for patients with hemodynamic collapse. It may be possible to prevent end-organ damage, thereby improving patients' survival.…”
Section: Casementioning
confidence: 99%